Pengaruh Work Environment Terhadap Job Satisfaction Dengan Work Relationship Sebagai Variabel Mediasi - Ratih Indriyani; Aksel Imanuel Iman (Fakultas Ekonomi Universitas PGRI Adi Buana, 2021)
This study aims to see the effect of work environment on job satisfaction in financing company employees in Ambon city with work relationship as a mediating variable. This is a quantitative study, involving 100 employees of 5 finance companies in Ambon city as respondents. This study is using partial least square, results show that work environment and work relationships have a significant effect on job satisfaction and work environment has a significant effect on work relationships among finance company employees in Ambon city.